Poverty and Social Exclusion: Key Challenges for Sustainable Rural Development in the New European Union Member States between 2007 and 2022 - Memo, Umutcan; Pieńkowski, Dariusz (Comparative Economic Research. Central and Eastern Europe, 2025)
Poverty has emerged as a significant global issue, impacting both urban and rural areas in developing countries. Its complex and multifaceted nature, encompassing profound economic, social, and psychological implications, has made addressing it even more challenging. Therefore, rural poverty is regarded as one of the most pressing challenges for achieving sustainable development within the European Union (EU). While the EU-15 countries (i.e., the “old” Member States) are relatively better positioned, rural poverty has remained a persistent issue in the “new” Member States, particularly in recent years. This study has examined the trends in rural poverty and social exclusion across the new EU Member States over the past 15 years. Using a data review methodology, it has analyzed rural poverty and exclusion trends from 2007 to 2022 in Bulgaria, Croatia, Czechia, Estonia, Hungary, Latvia, Lithuania, Poland, Romania, Slovakia, and Slovenia. The findings have revealed that Bulgaria, Croatia, Latvia, Lithuania, and Romania significantly lag behind the EU average in addressing rural poverty among the new member states.